2004
DOI: 10.1152/ajpendo.00313.2004
|View full text |Cite
|
Sign up to set email alerts
|

Portal infusion of a selective serotonin reuptake inhibitor enhances hepatic glucose disposal in conscious dogs

Abstract: Portal infusion of a selective serotonin reuptake inhibitor enhances hepatic glucose disposal in conscious dogs. Am J Physiol Endocrinol Metab 287: E1057-E1063, 2004. First published August 17, 2004 doi:10.1152/ajpendo.00313.2004.-Intraportal delivery of serotonin enhanced net hepatic glucose uptake (NHGU) during a hyperinsulinemic hyperglycemic clamp, but serotonin elevated catecholamines and can cause gastrointestinal distress. We hypothesized that the selective serotonin reuptake inhibitor (SSRI) fluvoxami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Studies were carried out in conscious 42-h-fasted dogs of either sex (20 -23 kg). This length of fast in the canine does not induce hypoglycemia, raise the plasma levels of stress hormones, or exhaust liver glycogen (38,39). In addition, after a 42-h fast approximately two-thirds of hepatic glucose production is accounted for by gluconeogenic flux (48), comparable with overnight-fasted humans.…”
mentioning
confidence: 99%
“…Studies were carried out in conscious 42-h-fasted dogs of either sex (20 -23 kg). This length of fast in the canine does not induce hypoglycemia, raise the plasma levels of stress hormones, or exhaust liver glycogen (38,39). In addition, after a 42-h fast approximately two-thirds of hepatic glucose production is accounted for by gluconeogenic flux (48), comparable with overnight-fasted humans.…”
mentioning
confidence: 99%
“…Physiological studies by Moore and colleagues demonstrated increased hepatic glucose uptake after intraportal infusion of 5-HT or selective 5-HT uptake inhibitors [12][13][14][15]. This raised the question whether these effects are mediated by a direct effect of 5-HT on hepatocytes or by indirect mechanisms involving haemodynamic changes or altered transmission of afferent signals.…”
Section: Discussionmentioning
confidence: 99%
“…The final DMSO concentration in all incubations was 0.1% v/v. For the determination of glycogen synthesis, glycolysis and glucose phosphorylation the medium was supplemented with [U- 14 C]glucose, [3-3 H]glucose or [2-3 H]glucose (37-74 kBq/ml) respectively. Glycogen synthesis was determined from the incorporation of 14 C label into glycogen, determined by ethanol precipitation [23], and glycolysis and glucose phosphorylation were determined from the rate of formation of 3 H 2 O [24].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments were conducted on twenty-one 42-h-fasted conscious mongrel dogs of either sex (18 -25 kg). This length of fast does not induce hypoglycemia, raise the plasma levels of stress hormones, or exhaust liver glycogen in the dog (42,43). Housing and diet have been described previously (21).…”
Section: Methodsmentioning
confidence: 99%